2.342   ODE No. 342

$x \left (2 e^{-x y(x)}+3 e^{x y(x)}\right ) \left (x y'(x)+y(x)\right )+1=0$ Mathematica : cpu = 0.525591 (sec), leaf count = 163

$\left \{\left \{y(x)\to -\frac {\cosh ^{-1}\left (\frac {1}{24} \left (-5 \sqrt {24+\log ^2\left (\frac {c_1}{x}\right )}-\log \left (\frac {c_1}{x}\right )\right )\right )}{x}\right \},\left \{y(x)\to \frac {\cosh ^{-1}\left (\frac {1}{24} \left (-5 \sqrt {24+\log ^2\left (\frac {c_1}{x}\right )}-\log \left (\frac {c_1}{x}\right )\right )\right )}{x}\right \},\left \{y(x)\to -\frac {\cosh ^{-1}\left (\frac {1}{24} \left (5 \sqrt {24+\log ^2\left (\frac {c_1}{x}\right )}-\log \left (\frac {c_1}{x}\right )\right )\right )}{x}\right \},\left \{y(x)\to \frac {\cosh ^{-1}\left (\frac {1}{24} \left (5 \sqrt {24+\log ^2\left (\frac {c_1}{x}\right )}-\log \left (\frac {c_1}{x}\right )\right )\right )}{x}\right \}\right \}$ Maple : cpu = 0.039 (sec), leaf count = 17

$\left \{ y \left ( x \right ) ={\frac {1}{x}\ln \left ( -{\frac {\ln \left ( x \right ) }{5}}+{\frac {{\it \_C1}}{5}} \right ) } \right \}$